2011
DOI: 10.1186/1471-2458-11-776
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial among cleaners-Effects on strength, balance and kinesiophobia

Abstract: BackgroundCleaners constitute a job group with poor health and low socioeconomic resources. Therefore, there is a great need for scientifically documented health promoting initiatives for cleaners. However, both workplace initiatives and high quality intervention studies are lacking. The aim of this study was to evaluate the effects of a 3-month workplace trial with interventions to improve physical or cognitive behavioural resources among cleaners.MethodsA cluster randomised controlled trial was conducted amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 45 publications
1
54
0
Order By: Relevance
“…The training programs also differed substantially in terms of normative standards, i.e., intensity of training stimuli, frequency of sessions, and amount of training. In at least three studies (20,24,27) the training schedule did not even meet the minimum standards of the World Health Organization (WHO) for strength-promoting exercise to prevent ill health (two sessions per week adding up to 75 min) (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The training programs also differed substantially in terms of normative standards, i.e., intensity of training stimuli, frequency of sessions, and amount of training. In at least three studies (20,24,27) the training schedule did not even meet the minimum standards of the World Health Organization (WHO) for strength-promoting exercise to prevent ill health (two sessions per week adding up to 75 min) (31).…”
Section: Discussionmentioning
confidence: 99%
“…After elimination of duplicates and scrutiny of study titles and abstracts, 68 articles remained for full-text analysis. Twelve publications fulfilled the selection criteria laid out in Table 1 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). The commonest reasons for exclusion were the absence of sex-specific analysis and the lack of muscle strength measurement.…”
Section: Study Selectionmentioning
confidence: 99%
“…Those participants having pain primarily related to the lower back participated in a programme with specific strengthening exercises corresponding to the strengthening exercises for the upper body. The standardised strengthening exercises for the lower back were exercises activating the rectus abdominis, erector spinae and oblique externus muscles for more than 60% of their maximal voluntary contraction [16,23]. During the intervention period, the training load was progressively increased.…”
Section: Tailored Physical Activity Group (Tpa)mentioning
confidence: 99%
“…pain situation, work ability, productivity, kinesiophobia and also outcomes measuring physical capacity. This physical activity intervention including both aerobic fitness training and strengthening exercises training was carefully chosen based on the results from previous research that have shown effective in other occupational groups [9,10,[15][16][17].…”
Section: International Journal Of Physical Medicine and Rehabilitationmentioning
confidence: 99%
“…PA interventions to improve muscle strength, stretch, and postural control, e.g., co-ordination training, may be particularly relevant for preventing osteoarticular deterioration in workers [13].…”
Section: Introductionmentioning
confidence: 99%